Shaping the Trans-Scale Properties of Schizophrenia via Cerebral Alterations on Magnetic Resonance Imaging and Single-Nucleotide Polymorphisms of Coding and Non-Coding Regions - Zhao, Shu-Wan; Xu, Xian; Wang, Xian-Yang; Yan, Tian-Cai; Cao, Yang; Yan, Qing-Hong; Chen, Kun; Jin, Yin-Chuan; Zhang, Ya-Hong; Yin, Hong; Cui, Long-Biao (Frontiers in Human Neuroscience, 2021)
Schizophrenia is a complex mental illness with genetic heterogeneity, which is often accompanied by alterations in brain structure and function. The neurobiological mechanism of schizophrenia associated with heredity remains unknown. Recently, the development of trans-scale and multi-omics methods that integrate gene and imaging information sheds new light on the nature of schizophrenia. In this paper, we summarized the the results of brain structural and functional changes related to the specific single nucleotide polymorphisms (SNPs) in the past decade, and the SNPs were divided into non-coding regions and coding regions to describe respectively. It is hoped that the relationship between SNPs and cerebral alteration can be displayed more clearly and intuitively, so as to provide fresh approaches for the discovery of potential biomarkers and the development of clinical accurate individualized treatment decision-making.